WECS Simulator for A Virtual Microgrid Laboratory - Cezara-Liliana RAT (Communications of International Proceedings, 2021)
The aim of this paper is to present a part of a virtual microgrid laboratory. This virtual laboratory has two functions: it constitutes a framework through which students can conduct experiments using simulation software and it also functions as a remote control to a physical microgrid laboratory. The virtual laboratory was implemented with the intention to teach students about power system and, particularly, renewable energy sources integrated within power systems. The virtual laboratory also includes such facilities as remote access for students to able to learn about and to experiment with power systems from home. The microgrid laboratory contains a wind energy conversion system (WECS) simulator as well as a PV panel simulator integrated in a grid-connected nanogrid. This paper presents a LabVIEW simulation of the WECS. This simulation is based on the real-time WECS Hardware-In-the-Loop (HIL) simulator being integrated in the virtual laboratory. The simulation program contains a wind turbine (WT), a permanent magnet synchronous generator (PMSG) and a load. The interaction between the PMSG and the load is complex and mathematical models are given on how to represent it in a programing environment such as LabVIEW. Mathematical models for the WT and the PMSG are also presented.
Keywords: WECS; PV; microgrid; PMSG.